2014
DOI: 10.1007/s00894-014-2335-0
|View full text |Cite
|
Sign up to set email alerts
|

The mechanistic study of the hydroxyl radical reaction with trans-2-chlorovinyldichloroarsine

Abstract: The trans-2-chlorovinyldichloroarsine (Lewisite) was produced and handled during WWI and WWII as chemical warfare agents. It was very difficult to explore its chemical characterization by experiments ways. The quantum chemical calculations proved to be a precise and harmless method for the toxicological system. In this paper, the gas phase reaction mechanisms of OH radical with trans-2-chlorovinyldichloroarsine (lewisite) were studied by second-order Møller-Plesset perturbation theory (MP2) method. The geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…330 Shi and co-workers showed that cis-1-propenylphosphoric acid potassium salt (735) could be epoxidized in 100% conversion and 74% ee using amine catalyst 737 and H 2 O 2 −CH 3 CN (Scheme 141). 331,332…”
Section: Chiral Amine or Chiral Amine Salt-catalyzed Epoxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…330 Shi and co-workers showed that cis-1-propenylphosphoric acid potassium salt (735) could be epoxidized in 100% conversion and 74% ee using amine catalyst 737 and H 2 O 2 −CH 3 CN (Scheme 141). 331,332…”
Section: Chiral Amine or Chiral Amine Salt-catalyzed Epoxidationmentioning
confidence: 99%
“…It was believed that the electronegative fluorine atom may stabilize ammonium salts through hydrogen bonding and charge–dipole interactions (Figure ), which was beneficial for the catalytic efficiency . Shi and co-workers showed that cis -1-propenylphosphoric acid potassium salt ( 735 ) could be epoxidized in 100% conversion and 74% ee using amine catalyst 737 and H 2 O 2 –CH 3 CN (Scheme ). , …”
Section: Organocatalyzed Asymmetric Epoxidation Of Olefinsmentioning
confidence: 99%
“…UV–vis absorption measurement is a common method to explore the structural change and acquire information of the complex formation . Figure shows UV–vis absorption spectra of HHb in the absence and presence of INH drug indicating a strong band in near‐UV region with a maximum 275 nm, which appears due to phenyl group of tryptophan (Trp) and tyrosine (Tyr) residues and another peak at 407 nm corresponds to the typical absorption of porphyrin‐soret band of HHb originated from heme groups, surrounded in a hydrophobic sack formed by the protein backbone through appropriate folding . The absorption peak at 275 nm of HHb‐INH system designates a slight shift toward shorter wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the main detoxification reaction involves the breaking of a As-Cl bond to form a new As-S bond producing a non-toxic stable species (2-methyl-1,3,2-dithio arsolan-4-yl methanol). Zhang et al(Zhang et al, 2014) investigated theoretically the reaction of OH radicals with lewisite. The reactions envisaged involved H and Cl-atom abstractions as well as an addition followed by an atom elimination.…”
Section: Introductionmentioning
confidence: 99%